Polydrug use of illicit drugs among adolescents in Hogar Crea of Barba de Heredia and Cartago - Murillo Castro, Ligia (2013)
The main objective of this research is to analyze polydrug use of illicit drugs in teenagers of both genders intwo nongovernmental organizations of Costa Rica. It depicts the problems with polydrug use with the qualitativeresearch using two focal groups of teenagers. They relate, with the technique of collage, their own experienceswith the way they use illicit drugs. The research showed that the most commonly used drugs are marihuana andcocaine mixed with tobacco, also the time they consume it goes from 2 months to 4 years. Furthermore, they facetheir recovery in a special center, assuming the experience with consuming brings negative consequences likedeath, crime and jail in some cases. However, they hope to defeat the addiction and look for a better future bygoing through with the program established in the organization and also with the support of their families.